Manuel Botelho, a musician in 17th century Évora - Henriques, Luís (2023)
A large number of musicians that worked in the cathedrals and main churches throughout the Portuguese Empire have remain almost anonymously to this day. This is the case of the musicians that worked in Évora during the sixteenth and seventeenth centuries. One such case is that of Manuel Botelho, an instrumentalist at the Cathedral during the first half of the seventeenth century. Recent evidence and research have provided new details on the life of this musician which presented here in the form of a short biographical note.